Inhibition of long noncoding RNA Gm41724 alleviates pressure overload-induced cardiac fibrosis by regulating lamina-associated polypeptide 2α. (February 2023) - Kong, Qihang; Zhou, Junteng; Ma, Chi; Wei, Zisong; Chen, Yan; Cheng, Yue; Wu, Wenchao; Zhou, Zhichao; Tang, Yong; Liu, Xiaojing
Abstract: Cardiac fibrosis is a pathological process underlying myocardial remodeling and is characterized by excessive deposition of the myocardial extracellular matrix. Long noncoding RNAs (lncRNAs) have emerged as critical regulators of various biological processes. In this study, we investigated the role of a novel lncRNA, Gm41724, in cardiac fibrosis induced by pressure overload. High-throughput whole transcriptome sequencing analysis was performed to detect differentially expressed lncRNAs in cardiac fibroblasts (CFs) with or without TGF-β1 treatment. Differential expression analysis and gene set enrichment analysis identified Gm41724 as a potential molecule targeting fibrosis. Gm41724 positively regulated the activation of CFs induced by TGF-β1 and pressure overload. Knocking down Gm41724 could inhibit the differentiation of CFs into myofibroblasts and alleviate cardiac fibrosis induced by pressure overload. Mechanistically, comprehensive identification of RNA-binding proteins by mass spectrometry (CHIRP-MS) and RNA immunoprecipitation (RIP) assay combined with other methods of molecular biological revealed the important role of Gm41724 binding to lamina-associated polypeptide 2α (lap2α) for the activation of CFs. Further mechanistic studies indicated that the regulator of G protein signaling 4 (Rgs4), as the downstream effector of Gm41724/lap2α, regulated CFs activation. Our results implicated the involvement of Gm41724 in cardiac fibrosis induced by pressure overload and it is expected to be a promising target for anti-fibrotic therapy. Graphical Abstract: Schematic presentation of the mechanism of lncRNA Gm41724 promoting cardiac fibrosis development. Under fibrotic stimuli such as TGF-β1, Gm41724 increases the expression of Rgs4 by binding to lap2α, which in turn induces the activation of CFs and cardiac fibrosis. ga1